2019
DOI: 10.3390/sym11080973
|View full text |Cite
|
Sign up to set email alerts
|

Ranking of Heritage Building Conversion Alternatives by Applying BIM and MCDM: A Case of Sapieha Palace in Vilnius

Abstract: A balance (symmetry) between socio-cultural and socio-economic benefits as a part of the economic, social, and cultural development policy of each city and country should be assured when converting built heritage. To anticipate building conversion priorities and opportunities, modern technologies can be employed. However, currently the activity of reconstruction of heritage buildings is part of the construction domain wherein modern digital technologies have been the least ever applied. Therefore, photogrammet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 56 publications
(81 reference statements)
0
21
0
3
Order By: Relevance
“…Architectural heritage resources are the most attractive to visitors [38], and several studies focused on how to rank heritage building conversion through experts' decision-making with multiple criteria [39,40]. This study indicated that heritage architecture, decoration, and style attracted visitors, though history and culture, cultural atmosphere, and well-preserved heritage were also important attractors.…”
Section: Theoretical Support For the Framework: Reuse Environmentmentioning
confidence: 96%
“…Architectural heritage resources are the most attractive to visitors [38], and several studies focused on how to rank heritage building conversion through experts' decision-making with multiple criteria [39,40]. This study indicated that heritage architecture, decoration, and style attracted visitors, though history and culture, cultural atmosphere, and well-preserved heritage were also important attractors.…”
Section: Theoretical Support For the Framework: Reuse Environmentmentioning
confidence: 96%
“…Spatial reuseThe ability of internal layout, spatial capacities, and infrastructure of abandoned architectural heritage for the new purpose; F 3 -Lifespan Duration of the building after restoration[28]; Architectural integrity Includes authenticity, originality, rarity, and architectural-compositional values of the heritage and its regime of protection; Refurbishment works The scope and the character of rehabilitation and restoration construction works[28] …”
mentioning
confidence: 99%
“…The most commonly used criteria for selecting appropriate new uses for heritage buildings are [1,28,34,52,53,[55][56][57][58]:…”
Section: Multi-criteria Decision Making Methods For Built Heritagementioning
confidence: 99%